Studies on hematological parameters in broiler chickens treated with 50% Amoxidem - D. Turcu,; Mariana Oporanu,; Grigorescu, P.,; Roman, M. (Medicamentul Veterinar, 2011)
Hematological response was studied in broiler chicken body as a consequence of treatment with Amoxidem 50% soluble powder. Under investigation were two batches of broiler chicken: control batch A andexperimental batch B that received Amoxidem 50% soluble powder 46mg/bw./day. Blood sampling was performed 7 days after treatment. The data were statistically analyzed using Student-Fisher method. The number of red blood cells showed no changes in statistical terms, the difference between batches being insignificant (p <0.5). Hemoglobin concentration in batch B increased significantly distinct (p <0.01) compared with batch A. Haematocrit showed similar values in both batches, the difference between them being insignificant (p <0.5). Constant erythrocyte MCV and MCHC values were statistically insignificant in the two batches (p <0.5). HEM concentration increased statistically significantly in batch B compared with batch A (p<0.05). The number of leukocytes in batch B showed an increase from batch A, the difference between them being statistically significant (p <0.05). The statistical difference between the two batches regarding the mean percentage of monocites is insignificant (p <0.5). In batch B there were changes that increase (p<0,001) ofneutrophils (heterophils) and highly significant decrease (p<0,001) of eosinophils.